Citizen Science in Libraries: A Co-Citation Analysis - Matijević, Ivana; Mumelaš, Dolores; Ivanjko, Tomislav (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie)

(untitled) (Canadian Association for Information Science - Association canadienne des sciences de l'information, 2026)
Citizen science, a core component of the open science movement, emphasizes public participation in scientific research and fosters inclusive, community-driven knowledge production. Libraries are increasingly recognized as critical facilitators of citizen science, offering infrastructure, support, and access to resources. This study investigates the intellectual structure of citizen science within the field of library and information science (LIS) through a co-citation analysis using data retrieved from Web of Science (WoS) and Scopus. The analysis identifies the most frequently co-cited authors and sources, revealing emerging research clusters and thematic trends. Findings show that while citizen science in LIS is a growing area of interest, the field remains relatively fragmented, with limited author interconnectivity and modest citation frequencies. The most frequently co-cited sources include journals focusing on academic and medical librarianship, highlighting the multidimensional relevance of citizen science across subfields. Keyword analysis reveals dominant themes such as open science, crowdsourcing, and digital humanities, which align with libraries’ evolving roles in participatory research. The study provides a comprehensive overview of current research dynamics and collaboration patterns, offering insights into the evolving role of libraries as active participants in citizen science initiatives.